Prevalensi dan Variasi Morfometrik Trichodina sp. pada Benih Ikan Gurami (Osphronemus gouramy Lac.) di Desa Rajapolah Tasikmalaya - Wildan Mukholladun; Rokhmani Rokhmani; Edy Riwidiharso (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Gurami (Osphronemusgouramy Lac.) Is a type of freshwater fish that is widely cultivated by the people of Indonesia. The high price of gouramy is a measure of consumption and the meat is tender and tasty. In Tasikmalaya, carp farmers in the cultivation of gouramy seeds are still experiencing problems. Gouramy seeds raised to adult size experience high mortality due to ectoparasites. One of the ectoparasites was Trichodina sp. Research has been conducted aimed at 1. Knowing the prevalence of gouramy seeds that were attacked by Trichodina sp. obtained from fish farmers in the village of Rajapolah, Tasikmalaya Regency and 2. Knowing the morphometric variations of Trichodina sp. found in gouramy seeds obtained from fish farmers in Rajapolah Village, Tasikmalaya Regency. The method used in this study is a survey method. Seed gourami aged 2 weeks is use as a sample. Isolation and identification were carried out by making a range preparation and painting using a 2% AgNO3 solution. The results found that the prevalence of 88% or high, while the results of the examination of morphometric variations found 4 species of trichodina sp. namely T. Pediculus, T. Nigra, T.heterodentata, and T. Acuta.Keywords:Trichodina sp., Gourami, morphometric variations, abundance, Rajapolah